Thermosensitive injectable in situ forming hydrogel incorporating anti-oxidative stress and anti-inflammatory nanoparticles for vital pulp therapy of pulpitis - Lixin Zhang; Xianling Ning; Jingyi Cui; Yanqiang Zhao; Fei Xie; Ningxin Zhu; Dan Wang; Man Qin; Zhiqiang Lin; Yuanyuan Wang (Materials Today Bio)
Vital pulp therapy is critically important for the long-term preservation of teeth with pulpitis. However, the anti-inflammatory effects of pulp-capping materials used in clinics remain unsatisfactory. Pulpitis is tightly connected with oxidative stresses; therefore, scavenging excessive reactive oxygen species (ROS) is a prospective treatment. Here a thermosensitive and injectable hydrogel that forms in situ was developed. By using poly(d,l-lactide)-poly(ethylene glycol)-poly(d,l-lactide)-based triblock copolymer (PPP) as a scaffold to carry Prussian blue nanoparticles (PBNPs), with effective ROS scavenging capability via multiple enzyme-like activities, such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD)activities. The developed PBNPs@PPP demonstrated anti-oxidative stress and anti-inflammation capabilities in vitro. As a direct pulp capping material, PBNPs@PPP suppressed inflammation progression in pulpitis in rats while also reducing cell necrosis and inflammatory cell infiltration in pulp tissue. RNA sequencing analyses showed that the functions of PBNPs@PPP were highly involved in anti-inflammatory pathways. Through experimental verification, it was found that PBNPs@PPP suppressed inflammation progression in pulpitis by inhibiting the NF-κB/NLRP3 pathway, which reduced the transmission of downstream inflammation pathways. Overall, use of this PBNPs@PPP hydrogel has potential to be a new, safe and efficient strategy for vital pulp therapy to treat pulpitis.